New Light on the Medieval Gough Map of Britain. Issue Volume 69:Issues 1(2017) (2nd January 2017) - Delano-Smith, Catherine; Barber, Peter; Bove, Damien; Clarkson, Christopher; Harvey, P. D. A.; Millea, Nick; Saul, Nigel; Shannon, William; Whittick, Christopher; Willoughby, James
ABSTRACT: Remarkably little is known about the earliest surviving separate-sheet medieval map of Britain that takes its name from its former owner, Richard Gough (1735–1809), and that has been variously dated to between 1300 and 1400, and later. It presents a sophisticated cartographical image at a time when detailed maps of individual regions were almost unknown in Europe, yet nothing is agreed about its possible origins, context (ecclesiastical or secular), or why and how it was compiled. In the belief that historical interpretation has to stem from an intimate knowledge of the map as artefact—the state of the parchment, nature of the inks, palaeography—as well as image, an informal study group of historians and scientists (the Gough Map Panel) was convened in 2012 to examine the map through high resolution digital reproduction, hyperspectral analysis, three-dimensional analysis and Raman pigment analysis. Although the study is still ongoing, much that is new has been discovered, notably about the way features were marked on the map, Gough's application to the map of a damaging reagent to render place-names readable, and the extent to which the original map (now dated to c .1400), although never completed, was nonetheless reworked on two different occasions in the fifteenth century, effectively creating two further maps. These and other findings are summarized here to encourage the further study of the map's features that is needed before it can be fully understood.